2015
DOI: 10.1037/fam0000063
|View full text |Cite
|
Sign up to set email alerts
|

Household chaos, sociodemographic risk, coparenting, and parent-infant relations during infants’ first year.

Abstract: Household chaos is a construct often overlooked in studies of human development, despite its theoretical links with the integrity of individual well-being, family processes, and child development. The present longitudinal study examined relations between household chaos and well-established correlates of chaos (sociodemographic risk, major life events, and personal distress) and several constructs that, to date, are theoretically linked with chaos but never before assessed as correlates (quality of coparenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
0
48
1
Order By: Relevance
“…Higher scores on positive coparenting indicated better quality of coparenting whereas higher scores on negative coparenting indicated worse coparenting quality. Whitesell, Teti, Crosby, & Kim (2015) found adequate reliability for positive and negative coparenting composites. Means and standard deviations at each time point are presented in Table 2.…”
Section: Methodsmentioning
confidence: 90%
“…Higher scores on positive coparenting indicated better quality of coparenting whereas higher scores on negative coparenting indicated worse coparenting quality. Whitesell, Teti, Crosby, & Kim (2015) found adequate reliability for positive and negative coparenting composites. Means and standard deviations at each time point are presented in Table 2.…”
Section: Methodsmentioning
confidence: 90%
“…Outcomes assessed included parenting, parent-child interactions, discipline, sibling relationships, parental response and reactions to child behaviours, family dysfunction, and food insecurity. Household chaos was associated with increased parent-child conflict, decreased parentchild closeness, decreased supportive parenting, decreased positive parenting, and increased negative parenting (88), in addition to less favourable co-parenting, and less emotional availability at bedtime (99). A chaotic home environment was also shown to be associated with less responsive and less stimulating parenting (89), less effective parental discipline (10), greater non-supportive responses to children's emotions and fewer supportive responses (76,94), and greater paternal hostility (95).…”
Section: Parenting and Family And Household Functioningmentioning
confidence: 98%
“…Twenty-one studies investigated the effects of household chaos on parenting and family functioning (4,10,46,76,(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102), of which five focused on the role of household chaos as a mediator or moderator. Outcomes assessed included parenting, parent-child interactions, discipline, sibling relationships, parental response and reactions to child behaviours, family dysfunction, and food insecurity.…”
Section: Parenting and Family And Household Functioningmentioning
confidence: 99%
“…Although it is correlated with SES, there is evidence that household chaos is a distinct construct and is associated with family variables above and beyond the associations with SES (Dumas et al, 2005). Studies have demonstrated links between household chaos and a variety of family outcomes such as decreased behavioural control in children (Vrijhof, van der Voort, Van IJzendoorn, & Euser, 2018), poor quality of coparenting (Whitesell, Teti, Crosby, & Kim, 2015), and negativity in the parent-child relationship (e.g., Kahn, Deater-Deckard, King-Casas, & Kim-Spoon, 2016;Nelson, O'Brien, Blankson, Calkins, & Keane, 2009). More specifically, and relevant to the current study, studies have demonstrated consistent links between household chaos and increased harsh parenting behaviours (e.g., Coldwell, Pike, & Dunn, 2006;Mills-Koonce et al, 2016;Pike, Atzaba-Poria, & Kretschmer, 2016;Zvara et al, 2014).…”
Section: Household Chaosmentioning
confidence: 99%